Water retention and soil moisture conservation biodegradable agricultural film with self-water-absorption structure and preparation method of water retention and soil moisture conservation biodegradable agricultural film
By using a combination of self-absorbent water structure and nanomaterials in agricultural films, the shortcomings of traditional agricultural films in water retention properties and mechanical strength are solved, and efficient water resource management and crop growth support are achieved.
Patent Information
- Application Number
- CN202411370658.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Traditional agricultural films have shortcomings in water retention, mechanical strength and hydrophobic and hydrophobic properties, which make it difficult to maintain soil moisture and the agricultural films are prone to damage, affecting crop growth and water resource utilization efficiency.
Biodegradable agricultural film using self-absorbent structure is composed of co-extrusion of the outer hydrophobic layer, intermediate mechanical support layer and inner hydrophilic layer. It is introduced by the hydrophobic layered nanosheets and super hydrophilic nanoparticles, combined with bidirectional Tensile coextrusion technology forms a multi-layer structure to improve water retention, hydrophobicity and mechanical properties.
It has achieved a comprehensive improvement in water retention, hydrophobicity and mechanical strength of agricultural films, extended the soil moisture retention time, improved the durability and water resource utilization efficiency of agricultural films, and is suitable for different environmental conditions.
Smart Images

Figure CN119261336A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable agricultural films, and more specifically to a biodegradable agricultural film with a self-water-absorbing structure for retaining water and moisture, and a preparation method thereof. Background Art
[0002] Conventional agricultural films represented by polyethylene (PE) have problems such as low recycling rate and long degradation cycle in the environment. Discarded plastic products continue to accumulate in the soil and are almost not degraded. Long-term use may also lead to soil compaction problems, thus affecting the growth and development of crops and harvest yields. Biodegradable materials, especially biodegradable polyesters, such as polylactic acid (PLA) and polybutylene adipate-co-terephthalate [PBAT], have become ideal choices to replace traditional plastics due to their excellent biodegradability and mechanical properties. However, single biodegradable polylactic acid materials show certain limitations in certain application scenarios, such as insufficient hydrophilicity, insufficient mechanical strength and poor barrier properties.
[0003] In agricultural film applications, traditional materials often have the following problems:
[0004] (1) Insufficient water retention: Traditional agricultural films have limited water retention and cannot effectively retain soil moisture, causing crop roots to dry out easily. They cannot meet the needs of modern agriculture for efficient use of water resources, especially in arid areas and in crops that require careful water management.
[0005] (2) Insufficient mechanical strength and toughness: Existing biodegradable agricultural film materials are insufficient in mechanical strength and toughness and are easily damaged or torn, causing the agricultural film to be easily damaged during use, affecting its service life and protective effect, and increasing the frequency and cost of replacement.
[0006] (3) It is difficult to balance hydrophilic and hydrophobic properties: It is difficult to achieve good hydrophilic and hydrophobic properties in agricultural films with existing technologies, which affects the overall water retention and durability of the agricultural films and cannot provide stable performance under different environmental conditions. Summary of the invention
[0007] In view of the above problems, the present invention provides a self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film and a preparation method thereof. The prepared agricultural film has the functions of water retention, hydrophobicity and hydrophilicity, and has excellent mechanical strength and toughness, and can meet the use requirements.
[0008] The first object of the present invention is to provide a self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film, which is composed of an outer hydrophobic layer, an intermediate mechanical support layer and an inner hydrophilic layer co-extruded.
[0009] The outer hydrophobic layer is composed of a hydrophobic layer masterbatch and polyester in a mass ratio of 5-9:1-5, and the mass ratio of the hydrophobic layer masterbatch to the polyester is 5:5, 6:4, 7:3, 8:2, 9:1, etc.
[0010] The hydrophobic layer masterbatch is prepared by blending and granulating the following components in parts by mass: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of hydrophobic layered nanosheets and 7 to 7.5 parts of auxiliary agents.
[0011] For example, the mass parts of polylactic acid are 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, etc.;
[0012] The mass parts of the hydrophobic layered nanosheets are 12.5 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, etc.
[0013] The mass parts of the auxiliary agent are 7 parts, 7.1 parts, 7.2 parts, 7.3 parts, 7.4 parts, 7.5 parts, etc.
[0014] The intermediate mechanical support layer is composed of a mechanical support layer masterbatch and polyester in a mass ratio of 5-9:1-5. For example, the mass ratio of the mechanical support layer masterbatch to the polyester is 5:5, 6:4, 7:3, 8:2, 9:1, etc.
[0015] The mechanical support layer masterbatch is prepared by blending and granulating the following components in parts by mass: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of bio-based filler and 7 to 7.5 parts of auxiliary agent.
[0016] For example, the mass parts of polylactic acid are 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, etc.
[0017] The mass parts of bio-based fillers are 12.5 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, etc.
[0018] The mass parts of the auxiliary agent are 7 parts, 7.1 parts, 7.2 parts, 7.3 parts, 7.4 parts, 7.5 parts, etc.
[0019] The inner hydrophilic layer is composed of a hydrophilic layer masterbatch and polyester in a mass ratio of 5 to 9:1 to 5. For example, the mass ratio of the hydrophilic layer masterbatch to the polyester is 5:5, 6:4, 7:3, 8:2, 9:1, and the like.
[0020] The hydrophilic layer masterbatch is prepared by blending and granulating the following components in parts by mass: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of superhydrophilic nanoparticles and 7 to 7.5 parts of auxiliary agents.
[0021] For example, the mass parts of polylactic acid are 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, etc.
[0022] The mass parts of superhydrophilic nanoparticles are 12.5 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, etc.
[0023] The weight parts of the auxiliary agent are 7 parts, 7.1 parts, 7.2 parts, 7.3 parts, 7.4 parts, 7.5 parts, etc. However, the above values are not limited to the above values, and other values not listed in the above value range are also applicable.
[0024] In a preferred embodiment of the present invention, the hydrophobic layered nanosheets are prepared according to the following steps:
[0025] The layered silicate mineral, a hydrophobic surfactant and a fluorinating agent are subjected to shear exfoliation to cause a fluorination reaction, thereby introducing fluorine groups into the layered silicate mineral to obtain hydrophobic layered nanosheets.
[0026] The mass ratio of the layered silicate mineral to the fluoriding agent is 100:0.1 to 10; for example, the mass ratio of the layered silicate mineral to the fluoriding agent is 100:0.1, 100:2, 100:4, 100:6, 100:8, 100:10, etc.
[0027] The mass ratio of the layered silicate mineral to the hydrophobic surfactant is 100:0.1-5; for example, the mass ratio of the layered silicate mineral to the hydrophobic surfactant is 100:0.1, 100:1, 100:2, 100:3, 100:4, 100:5, etc.
[0028] Shear peeling is performed by grinding at 20°C to 80°C for 20 min to 120 min. For example, the grinding temperature is 20°C, 40°C, 60°C, 80°C, etc., and the grinding time is 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, etc.; but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0029] In a preferred embodiment of the present invention, superhydrophilic nanoparticles are prepared according to the following steps:
[0030] In a solvent system, hydrophilic nanoparticles, a hydrophilic bridging agent and a hydrophilic surfactant are mixed, and under the assistance of microwaves, condensation and covalent bonding reactions occur to introduce the hydrophilic groups of the hydrophilic surfactant into the surface of the hydrophilic nanoparticles to prepare super-hydrophilic nanoparticles.
[0031] In a preferred embodiment of the present invention, the mass ratio of hydrophilic nanoparticles to hydrophilic bridging agent is 70-100:5-30; for example, the mass ratio of hydrophilic nanoparticles to hydrophilic bridging agent is 70:30, 80:20, 90:10, 100:5, etc.
[0032] The mass ratio of hydrophilic nanoparticles to hydrophilic surfactants is 1:0.01 to 0.1; for example, the mass ratio of hydrophilic nanoparticles to hydrophilic surfactants is 1:0.01, 1:0.02, 1:0.04, 1:0.06, 1:0.08, 1:0.1, etc.
[0033] In the condensation and covalent bonding reactions, the microwave output power is 100W to 1500W, for example, the microwave output power is 100W, 300W, 600W, 900W, 1200W, 1500W, etc.
[0034] The reaction temperature is 80°C to 200°C, for example, the reaction temperature is 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, etc.
[0035] The reaction time is 20 min to 120 min, for example, the reaction time is 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0036] In a preferred embodiment of the present invention, the hydrophobic layer masterbatch accounts for 15% to 30% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; for example, the hydrophobic layer masterbatch accounts for 15%, 20%, 25%, 30%, etc. of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch.
[0037] The mechanical support layer masterbatch accounts for 35% to 60% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; for example, the mechanical support layer masterbatch accounts for 35%, 40%, 45%, 50%, 55%, 60% and the like of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch.
[0038] The hydrophilic layer masterbatch accounts for 20% to 35% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; for example, the hydrophilic layer masterbatch accounts for 20%, 25%, 30%, 35% and the like of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0039] The total amount of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch is 100%.
[0040] In a preferred embodiment of the present invention, the bio-based filler is one or more of wood fiber, bamboo fiber and corn straw.
[0041] The additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, and the additives are composed of the following components by mass: 4 to 5 parts of plasticizer, 0.5 to 1 part of antioxidant, 0.5 to 1 part of ultraviolet absorber, 0.5 to 1 part of heat stabilizer and 0.5 to 1 part of dye.
[0042] For example, the plasticizer is 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, etc.
[0043] The antioxidant is 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc.
[0044] The amount of the ultraviolet absorber is 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0045] The amount of heat stabilizer is 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0046] The dye is 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc.; but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0047] The polyester is one or more of polybutylene succinate, polyhydroxyalkanoate, polyethylene terephthalate / polycaprolactone blend and polycaprolactone.
[0048] The second object of the present invention is to provide a method for preparing the above-mentioned self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film, comprising the following steps:
[0049] The components of the hydrophobic layer masterbatch are weighed according to the following mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of hydrophobic layered nanosheets and 7-7.5 parts of auxiliary agents; the polylactic acid, hydrophobic layered nanosheets and auxiliary agents are blended and granulated to obtain the hydrophobic layer masterbatch.
[0050] The components of the mechanical support layer masterbatch are weighed according to the following parts by mass: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of bio-based fillers and 7 to 7.5 parts of additives; the polylactic acid, bio-based fillers and additives are blended and granulated to obtain the mechanical support layer masterbatch.
[0051] The components of the hydrophilic layer masterbatch are weighed according to the following mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of superhydrophilic nanoparticles and 7-7.5 parts of auxiliary agents; the polylactic acid, superhydrophilic nanoparticles and auxiliary agents are blended and granulated to obtain the hydrophilic layer masterbatch.
[0052] The hydrophobic layer masterbatch and polyester are melt-blended to obtain a first masterbatch, the mechanical support layer masterbatch and polyester are melt-blended to obtain a second masterbatch, the hydrophilic layer masterbatch and polyester are melt-blended to obtain a third masterbatch, and the first masterbatch, the second masterbatch and the third masterbatch are co-extruded by biaxial stretching to obtain a water-retaining biodegradable agricultural film with a self-absorbent structure.
[0053] In a preferred embodiment of the present invention, when preparing the first masterbatch, the second masterbatch and the third masterbatch, the melt blending temperature and time are the same, and the melt blending temperature is 120°C to 300°C. For example, the blending temperature is 120°C, 160°C, 200°C, 240°C, 280°C, 300°C, etc.
[0054] The melt blending time is 10 min to 120 min; for example, the mixing time is 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0055] In a preferred embodiment of the present invention, in the biaxial stretching co-extrusion step, the extrusion die temperature is 170°C to 200°C; for example, the extrusion die temperature is 170°C, 180°C, 190°C, 200°C, etc.
[0056] The longitudinal preheating temperature is 60°C to 90°C; for example, the longitudinal preheating temperature is 60°C, 70°C, 80°C, 90°C, etc.
[0057] The longitudinal cooling temperature is 20°C to 40°C; for example, the longitudinal cooling temperature is 20°C, 30°C, 40°C, etc.
[0058] The longitudinal stretching temperature is 90° C. to 130° C., for example, the longitudinal stretching temperature is 90° C., 100° C., 110° C., 120° C., 130° C., etc.
[0059] The longitudinal drawing setting temperature is 80°C to 120°C; for example, the longitudinal drawing setting temperature is 80°C, 90°C, 100°C, 110°C, 120°C, etc.
[0060] The longitudinal stretching ratio is 1.5 to 3 times; for example, the longitudinal stretching ratio is 1.5, 2, 2.5, 3, etc.
[0061] The transverse preheating temperature is 70°C to 110°C; for example, the transverse preheating temperature is 70°C, 80°C, 90°C, 100°C, 110°C, etc.
[0062] The transverse stretching temperature is 90°C to 130°C; for example, the transverse stretching temperature is 90°C, 100°C, 110°C, 120°C, 130°C, etc.
[0063] The transverse heat setting temperature is 100° C. to 140° C., for example, the heat setting temperature is 100° C., 110° C., 120° C., 130° C., 140° C., etc.
[0064] The transverse cooling temperature is 20°C to 50°C; for example, the transverse cooling temperature is 20°C, 30°C, 40°C, 50°C, etc.
[0065] The transverse stretching ratio is 1.5 to 4 times, for example, the transverse stretching ratio is 1.5, 2, 2.5, 3, 3.5, 4, etc.; but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0066] In a preferred embodiment of the present invention, the method further comprises subjecting the surface of the hydrophilic layer of the composite film obtained by biaxial stretching co-extrusion to oxygen plasma treatment.
[0067] The oxygen plasma treatment is carried out at 500W to 1500W for 0.5min to 20min. For example, the power of the oxygen plasma treatment is 500W, 700W, 900W, 1100W, 1300W, 1500W, etc., and the reaction time is 0.5min, 5min, 10min, 15min, 20min, etc., but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] (1) The present invention provides a self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film, which consists of an outer hydrophobic layer, an intermediate mechanical support layer and an inner hydrophilic layer. The hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are melt-blended with polyester respectively and then co-extruded. The different materials are prepared by rearrangement of molecular chains and interface bonding to obtain a multilayer structure having an inner hydrophilic layer, an intermediate mechanical support layer and an outer hydrophobic layer. The addition of the hydrophobic layer masterbatch blocks moisture from the external environment and reduces water loss, thereby improving the water-retaining effect of the agricultural film. The function of the mechanical support layer masterbatch is to provide the entire agricultural film with the necessary mechanical strength, toughness and stability. The introduction of the hydrophilic layer masterbatch is to give the agricultural film the ability to absorb water by itself. Ultimately, the prepared agricultural film can simultaneously have the functions of water retention, hydrophobicity, hydrophilicity and mechanical support, meet multiple functional requirements, and improve the comprehensive performance of the agricultural film.
[0070] (2) The present invention places layered silicate minerals, surfactants and fluorinated agents in a shear stripping device for grinding to obtain hydrophobic layered nanosheets, which have excellent hydrophobic properties, can effectively prevent water evaporation, and improve the water retention performance of agricultural films; through microwave-assisted in-situ functionalization technology, hydrophilic groups are introduced on the surface of hydrophilic nanoparticles to prepare superhydrophilic nanoparticles, which can quickly absorb and retain water, enhance the overall water retention capacity of agricultural films, and are particularly suitable for crops that require a high-water environment. And these superhydrophilic nanoparticles and hydrophobic layered nanosheets are uniformly dispersed in a polymer matrix using the method of the present invention. The full stripping, uniform dispersion and network construction of nanoparticles are achieved, which effectively improves the secondary utilization of water, and at the same time significantly improves the mechanical properties of composite materials, greatly expanding the scope of application.
[0071] (3) The use of high-toughness biodegradable polyester materials, through the introduction of hydrophobic layered nanosheets and super-hydrophilic nanoparticles, improves the toughness and ductility of the composite material, ensuring the impact toughness of the material in a low-temperature environment. This high-toughness biodegradable material ensures the balance of mechanical properties of the composite material, which is the prerequisite for large-scale mechanized continuous coating applications.
[0072] (4) The present invention adopts a biaxial stretching co-extrusion method to prepare a multi-layer biodegradable film during multi-layer co-extrusion. The biaxial stretching technology improves the mechanical strength and toughness of the agricultural film, making it more durable and less prone to damage during use, thus meeting the requirements for large-scale application of mechanized continuous coating.
[0073] The present invention adopts a multi-layer structure design, including an outer hydrophobic layer, an intermediate mechanical support layer and an inner hydrophilic layer. The inner hydrophilic layer absorbs water from the soil through close contact with the soil. When the water in the soil evaporates, the water vapor can enter the inner hydrophilic layer through the bottom or side of the agricultural film, and the inner hydrophilic layer stores the water and slowly releases it into the soil to ensure that crops can also obtain water during droughts; the main function of the outer hydrophobic layer is to prevent the water in the external environment from entering the inside of the agricultural film, while reducing the evaporation of water in the film to the outside. Through the external hydrophobic layer, the agricultural film can avoid excessive water absorption caused by high humidity or rain in the outside world, while maintaining the stability of internal water. The external hydrophobic layer also plays a certain protective role, preventing external pollutants or mechanical damage from affecting the internal structure of the film. This design not only improves the comprehensive performance of the film, but also ensures its stable performance under different environmental conditions, and expands its wider application in different regions.
[0074] The present invention also performs oxygen plasma treatment on the surface of the internal hydrophilic layer to enhance the hydrophilicity of the film. The oxygen plasma treatment significantly improves the hydrophilicity of the film surface, allowing the agricultural film to more effectively absorb and retain moisture, further enhancing its water retention performance and durability.
[0075] (5) The present invention adopts a technical route combining high shear blending and high-ratio stretching to ensure clean, continuous and large-scale production of nanocomposites. This process can be quickly industrialized and low-cost on existing conventional processing equipment, significantly reducing manufacturing costs and improving production efficiency.
[0076] (6) The method of the present invention has strong adaptability and can be widely used in the processing of nanocomposite materials of other systems. At the same time, the use of all-biodegradable materials ensures that the agricultural film will not cause soil compaction and fertility decline after use, which is in line with the concept of environmental protection and sustainable development, avoids the environmental pollution problems of traditional agricultural films, and has a positive effect on promoting the large-scale production and application of nanocomposite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 The present invention is a flow chart for preparing a biodegradable agricultural film with a self-water-absorbing structure and moisture-retaining properties.
[0078] Figure 2 The present invention is a flow chart for preparing hydrophobic layered nanosheets.
[0079] Figure 3 The present invention is a flow chart for preparing superhydrophilic nanoparticles. DETAILED DESCRIPTION
[0080] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0081] A self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film is composed of an outer hydrophobic layer, an intermediate mechanical support layer and an inner hydrophilic layer which are co-extruded.
[0082] The outer hydrophobic layer is composed of a hydrophobic layer masterbatch and polyester in a mass ratio of 5-9:1-5. The hydrophobic layer masterbatch is made by blending and granulating the following components in mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of hydrophobic layered nanosheets and 7-7.5 parts of additives.
[0083] The intermediate mechanical support layer is composed of a mechanical support layer masterbatch and polyester in a mass ratio of 5-9:1-5. The mechanical support layer masterbatch is made by blending and granulating the following components in mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of bio-based filler and 7-7.5 parts of additives.
[0084] The inner hydrophilic layer is composed of a hydrophilic layer masterbatch and polyester in a mass ratio of 5-9:1-5. The hydrophilic layer masterbatch is made by blending and granulating the following components in mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of superhydrophilic nanoparticles and 7-7.5 parts of additives.
[0085] The masterbatch used in the present invention is composed of a hydrophobic layer masterbatch, a support layer masterbatch and a hydrophilic layer masterbatch. In the structure, the hydrophobic layer masterbatch is mainly responsible for preventing water from evaporating too quickly from the soil. It reduces water loss by blocking moisture from the external environment, thereby improving the water retention effect of the agricultural film. The hydrophobic layer not only prolongs the water retention time in the soil, but also reduces the need for frequent irrigation due to water loss, thereby helping to save water.
[0086] The function of the mechanical support layer masterbatch is to provide the necessary mechanical strength and stability for the entire agricultural film. The biaxial stretching process rearranges the molecular chains of the material and forms a dense structure through interface bonding, which not only enhances the tensile strength and durability of the agricultural film, but also improves its resistance to external pressure and tension during use. The presence of the intermediate mechanical support layer ensures that the agricultural film can maintain its functionality and stability in various environments.
[0087] The introduction of the hydrophilic layer masterbatch is to give the agricultural film the ability to absorb water. This layer can effectively absorb and retain water through the hydrophilicity of the material surface, transfer it to the underlying soil, and ensure the water supply of plant roots. The design of the hydrophilic layer not only promotes the effective use of water, but also reduces the evaporation of water on the soil surface, further enhancing the moisture retention effect.
[0088] Through the rational combination of these masterbatches and the application of multi-layer co-extrusion technology, different materials form a stable multi-layer structure through the rearrangement of molecular chains and interface bonding. This structure has the ability to retain water, retain moisture and absorb water while ensuring mechanical properties. This innovative design allows agricultural films to reduce water consumption, increase crop yields, and achieve complete biodegradation after use, meeting environmental protection requirements.
[0089] The super-hydrophilic nanoparticles of the present invention should have a particle size between 1 and 100 nm and a uniform particle size distribution, and have a high specific surface area to provide more hydrophilic active sites, and have good thermal stability to withstand the higher temperatures during the processing of polylactic acid.
[0090] The process of composite modification of layered silicate and super-hydrophilic nanoparticles combined with multi-layer co-extrusion technology significantly improves its water retention performance by introducing Janus structure and self-absorption function, realizes the secondary utilization of rainwater, and improves the efficiency of water resource utilization. It is particularly suitable for arid and water-scarce areas and promotes the sustainable development of agriculture.
[0091] Further, such as Figure 2 As shown, the hydrophobic layered nanosheets are prepared according to the following steps:
[0092] The layered silicate mineral, the hydrophobic surfactant and the fluorinating agent are shear-stripped to produce a fluorination reaction to obtain a hydrophobic layered nanosheet. The fluorinating agent forms Si-O-Si bonds with the hydroxyl groups on the surface of the silicate mineral, and reacts with other active groups to form CF bonds or Si-F bonds, that is, low surface energy fluorine groups are introduced on the surface of the layered silicate mineral, making the mineral surface hydrophobic.
[0093] In the shearing and peeling process of the present invention, the hydrophobic surfactant is adsorbed on the surface of the nanosheets through electrostatic or van der Waals forces, thereby preventing the nanosheets from re-aggregating and ensuring their dispersibility.
[0094] Preferably, in the shearing and stripping step, the solvent used is an organic solvent, such as one or more of anhydrous ethanol, acetone, xylene, methanol, ether, etc.
[0095] The shearing stripping method includes high-pressure homogenization, ultrasonic stripping, liquid phase circulation high-speed shearing, high-speed centrifugation, etc. The particle size of the obtained hydrophobic layered nanosheets is 50-100nm.
[0096] The separation method after shearing and stripping is one of precipitation, filtration, membrane separation, centrifugation and the like.
[0097] Furthermore, the mass ratio of the layered silicate mineral to the fluorinating agent is 100:0.1-10; the mass ratio of the layered silicate mineral to the hydrophobic surfactant is 100:0.1-5, and the shear exfoliation is performed by grinding at 20°C-80°C for 20min-120min.
[0098] Preferably, the layered silicate mineral is one or more of montmorillonite, kaolinite, illite and vermiculite, wherein the maximum radial dimension is 100 to 2000 nm and the thickness is 1 nm to 10 nm.
[0099] The fluorinating agent is one or more of perfluorooctanethiol, perfluorooctyltriethoxysilane, perfluorooctylethyltrioxysilane, perfluorooctanesulfonyl fluoride and perfluorooctylpropylene.
[0100] The hydrophobic surfactant is one or more of sodium dodecylbenzene sulfonate, sodium hexadecylbenzene sulfonate, sodium dodecyl sulfate and sodium dodecyl polyoxyethylene ether sulfate.
[0101] Furthermore, superhydrophilic nanoparticles are prepared by microwave-assisted reaction. The hydrophilic bridging agent is heated by microwave to efficiently and uniformly introduce hydrophilic groups into the surface of the nanoparticles through Si-O-Si bonds to form highly hydrophilic nanomaterials. At the same time, the surfactant maintains the dispersibility of the nanoparticles.
[0102] like Figure 3 As shown, it is prepared according to the following steps:
[0103] In a solvent system, hydrophilic nanoparticles, a hydrophilic bridging agent and a hydrophilic surfactant are mixed, and condensation and covalent bonding reactions occur under the assistance of microwaves. The hydrophilic groups (such as amino groups) of the surfactant are introduced into the surface of the hydrophilic nanoparticles through the synergistic effect of the hydrophilic bridging agent and the hydrophilic surfactant to prepare super hydrophilic nanoparticles.
[0104] Condensation reaction: The silane groups in the hydrophilic bridging agent react with the hydroxyl groups on the surface of the nanoparticles to form silicon-oxygen bonds, which are stably bound to the surface of the nanoparticles.
[0105] Covalent bonding: The hydrophilic groups in the surfactant covalently bond with the functional groups (such as amino or hydroxyl groups) on the surface of the bridging agent to further modify the surface.
[0106] Hydrogen bonding: Hydrophilic groups interact with water molecules through hydrogen bonds, enhancing the hydrophilicity of the material.
[0107] Furthermore, the mass ratio of the hydrophilic nanoparticles to the hydrophilic bridging agent is 70-100:5-30; the mass ratio of the hydrophilic nanoparticles to the hydrophilic surfactant is 1:0.01-0.1.
[0108] It is understood that the present invention has no particular restrictions on the type and source of hydrophilic nanoparticles. Those skilled in the art can select and adjust according to the actual application, product quality and product performance. The hydrophilic nanoparticles used in the present invention are hydrophilic SiO2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a product number of S861488, a particle size of 15 nm, and a specific surface area of 300±50 m 2 / g.
[0109] In the condensation and covalent bonding reactions, the microwave output power is 500W to 1500W, the reaction temperature is 80°C to 200°C, and the reaction time is 20min to 120min.
[0110] Preferably, the hydrophilic bridging agent is one or more of 3-aminopropyltriethoxysilane (AMEO), 3-glycidyloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and the like.
[0111] The hydrophilic surfactant is one or more of hexadecyl trimethyl ammonium bromide (CTAB), dodecyl trimethyl ammonium bromide (DTAB), sodium dodecyl sulfate (SDS) and cocamidopropyl betaine.
[0112] The hydrophobic layer masterbatch accounts for 15% to 30% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch.
[0113] The mechanical support layer masterbatch accounts for 35% to 60% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch.
[0114] The hydrophilic layer masterbatch accounts for 20% to 35% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch total 100%.
[0115] Furthermore, the bio-based filler is one or more of wood fiber, bamboo fiber, straw fiber, lignin, chitosan, coconut shell fiber and hemp fiber.
[0116] The additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, and the additives are composed of the following components by mass: 4 to 5 parts of plasticizer, 0.5 to 1 part of antioxidant, 0.5 to 1 part of ultraviolet absorber, 0.5 to 1 part of heat stabilizer and 0.5 to 1 part of dye.
[0117] Among them, the plasticizer is epoxy ester, triethyl citrate or white oil; the antioxidant is an antioxidant phenolic antioxidant, such as antioxidant BHT, antioxidant 168, antioxidant 300, antioxidant 1010, p-phenylenediamine, antioxidant phenolic antioxidant, tri(2,4-di-tert-butylphenyl) phosphate or dilauryl thiodipropionate; the ultraviolet absorber is UV-327 or UV-531, hydroxybenzotriazole compounds, lignin derivatives, nano zinc oxide, nano titanium dioxide, UV-327, UV-531 or benzothiazole compounds; the heat stabilizer is stearic acid, stearate; the dye is carbon black, iron oxide pigment, titanium dioxide or phthalocyanine blue.
[0118] The use of plasticizers in additives can improve the flexibility and processability of polylactic acid, the use of antioxidants can prevent the degradation of polylactic acid during processing and use, the use of UV absorbers can protect the material from UV degradation, the use of heat stabilizers can improve the stability of the material during high-temperature processing, and the use of dyes can be used to dye agricultural films. Dark colors are more conducive to inhibiting soil moisture evaporation and inhibiting weed growth.
[0119] The polyester is one or more of polybutylene succinate [poly(butylene succinate), PBS], poly(butylene adipate-co-terephthalate), PBAT, polyhydroxyalkanoate and polycaprolactone. The molecular weight of polybutylene succinate used in the present invention is 50,000 to 150,000, and the CAS number is 25777-14-4; the molecular weight of polybutylene terephthalate-adipate is 120,000, and the CAS number is 55231-08-8. The molecular weight of polycaprolactone is 80,000, and the CAS number is 24980-41-4. The molecular weight of polyhydroxyalkanoate is 250,000, which can be purchased from Wuhan Shuer Biotechnology Co., Ltd.
[0120] The present invention also provides a method for preparing a self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film, such as Figure 1 As shown, the following steps are included:
[0121] The components of the hydrophobic layer masterbatch are weighed according to the following mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of hydrophobic layered nanosheets and 7-7.5 parts of auxiliary agents; the polylactic acid, hydrophobic layered nanosheets and auxiliary agents are blended and granulated to obtain the hydrophobic layer masterbatch.
[0122] The components of the mechanical support layer masterbatch are weighed according to the following mass parts: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of bio-based fillers and 7 to 7.5 parts of additives; the polylactic acid, bio-based fillers and additives are blended and granulated to obtain the mechanical support layer masterbatch.
[0123] The components of the hydrophilic layer masterbatch are weighed according to the following mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of superhydrophilic nanoparticles and 7-7.5 parts of auxiliary agents; the polylactic acid, superhydrophilic nanoparticles and auxiliary agents are blended and granulated to obtain the hydrophilic layer masterbatch.
[0124] The hydrophobic layer masterbatch and polyester are melt-blended to obtain the first masterbatch, the mechanical support layer masterbatch and polyester are melt-blended to obtain the second masterbatch, and the hydrophilic layer masterbatch and polyester are melt-blended to obtain the third masterbatch. The first masterbatch, the second masterbatch and the third masterbatch are co-extruded by biaxial stretching to obtain a self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film. During the stretching process, each layer of material forms a stable multilayer structure through the rearrangement of molecular chains and interface bonding.
[0125] When preparing the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch, the blending equipment is at least one of a reciprocating screw extruder, a twin-screw extruder, a high-speed mixer, an open mixer, a tumble mixer, a continuous mixer, a Z-type kneader, a screw kneader, a vacuum kneader and a horizontal twin-screw mixer.
[0126] Furthermore, when preparing the first masterbatch, the second masterbatch and the third masterbatch, the melt blending temperature and time are the same, the melt blending temperature is 120° C. to 300° C., and the melt blending time is 10 min to 120 min.
[0127] Furthermore, in the biaxial stretching co-extrusion step, the extrusion die temperature is 170°C to 200°C.
[0128] The longitudinal preheating temperature is 60℃~90℃, the longitudinal cooling temperature is 20℃~40℃, the longitudinal stretching temperature is 90℃~130℃, and the longitudinal drawing setting temperature is 80℃~120℃.
[0129] The transverse preheating temperature is 70°C to 110°C, the transverse stretching temperature is 100°C to 140°C, the transverse heat setting temperature is 100°C to 140°C, and the transverse cooling temperature is 20°C to 50°C.
[0130] The transverse stretching ratio is 1.5 to 4 times, and the longitudinal stretching ratio is 1.5 to 3 times.
[0131] Furthermore, the method further comprises subjecting the surface of the hydrophilic layer of the composite film obtained by biaxial stretching co-extrusion to oxygen plasma treatment; the oxygen plasma treatment is carried out at 500W to 1500W for a reaction time of 0.5min to 20min.
[0132] Example 1
[0133] A highly water-retaining biodegradable agricultural film with a self-absorbent structure, comprising the following raw materials in parts by weight:
[0134] Hydrophobic layer masterbatch: 80 parts of polylactic acid, 12.5 parts of hydrophobic montmorillonite nanosheets, and 7.5 parts of additives.
[0135] Mechanical support layer masterbatch: 80 parts of polylactic acid, 12.5 parts of wood fiber, and 7.5 parts of additives.
[0136] Hydrophilic layer masterbatch: 80 parts of polylactic acid, 12.5 parts of super hydrophilic SiO2 nanoparticles, and 7.5 parts of additives.
[0137] Among them, the additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, consisting of 5 parts of epoxidized soybean oil, 0.5 parts of antioxidant BHT, 0.5 parts of UV-327, 0.5 parts of zinc stearic acid, and 1 part of carbon black.
[0138] The preparation method comprises the following steps:
[0139] S1. 100 g of montmorillonite was added to an ether solution to prepare a solution with a mass concentration of 0.1 wt%, and then 1 g of sodium dodecylbenzene sulfonate and 0.2 g of perfluorooctanethiol were added. The solution was ground at 25 ° C for 30 min using a turbine sand mill with a working energy consumption of 1 kWh / kg, and hydrophobic montmorillonite nanosheets with a particle size of 100 nm were obtained by centrifugal separation.
[0140] S2. 100g of hydrophilic SiO2 nanoparticles were added to anhydrous ethanol to prepare a solution with a mass concentration of 0.1wt%, and then 5g of 3-aminopropyltriethoxysilane and 1g of CTAB were added and dispersed in anhydrous ethanol. Hydrophilic groups were introduced on the surface of the hydrophilic nanoparticles with the assistance of microwaves. The output power of the microwave reactor was 1500W, the reaction temperature was 200℃, and the reaction time was 20min to prepare super hydrophilic SiO2 nanoparticles.
[0141] S3. Add 80 parts of polylactic acid, 12.5 parts of hydrophobic montmorillonite nanosheets, and 7.5 parts of additives into a high-speed mixer and mix them at 150°C for 60 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 0.1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0142] 80 parts of polylactic acid, 12.5 parts of wood fiber and 7.5 parts of additives were added into a high-speed mixer for hot mixing at 150°C for 60 minutes. When the ratio of mixing output energy to the mass of all mixtures reached 0.1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0143] 80 parts of polylactic acid, 12.5 parts of super-hydrophilic SiO2 nanoparticles and 7.5 parts of additives were added into a high-speed mixer for hot mixing at 150°C for 60 minutes. When the ratio of mixing output energy to the mass of all the mixture reached 0.1 kWh / kg, a hydrophilic layer masterbatch was obtained.
[0144] S4. Weigh 15% of the hydrophobic layer masterbatch, 60% of the mechanical support layer masterbatch, and 25% of the hydrophilic layer masterbatch according to mass percentage, and melt-blend the weighed hydrophobic layer masterbatch and PBS at a mass ratio of 7:3 at 180° C. to obtain a first masterbatch.
[0145] The mechanical support layer masterbatch and PBS were melt-blended at 180° C. in a mass ratio of 7:3 to obtain a second masterbatch.
[0146] The hydrophilic layer masterbatch and PBS were melt-blended at 180° C. in a mass ratio of 7:3 to obtain a third masterbatch.
[0147] The first masterbatch, the second masterbatch and the third masterbatch are added from different feed ports and co-extruded by biaxial stretching, and the extrusion die temperature is 200°C.
[0148] The longitudinal preheating temperature is 90°C, the longitudinal stretching temperature is 100°C, the longitudinal drawing setting temperature is 120°C, the longitudinal cooling temperature is 40°C, and the longitudinal stretching ratio is 3 times.
[0149] The transverse preheating temperature is 110°C, the transverse stretching temperature is 130°C, the transverse heat setting temperature is 140°C, the transverse cooling temperature is 50°C, and the transverse stretching ratio is 1.5 times to prepare a composite membrane. The composite membrane is divided into three layers from the inside to the outside, namely, an inner hydrophilic layer, a middle mechanical support layer and an outer hydrophobic layer.
[0150] Subsequently, the surface of the inner hydrophilic layer was treated with oxygen plasma at 500 W for 10 min to prepare a self-watering, highly moisturizing biodegradable agricultural film with a thickness of 50 μm.
[0151] Example 2
[0152] A highly water-retaining biodegradable agricultural film with a self-absorbent structure, comprising the following raw materials in parts by weight:
[0153] Hydrophobic layer masterbatch: 75 parts of polylactic acid, 18 parts of hydrophobic kaolinite, and 7 parts of additives.
[0154] Mechanical support layer masterbatch: 75 parts of polylactic acid, 18 parts of bamboo fiber, and 7 parts of additives.
[0155] Hydrophilic layer masterbatch: 75 parts of polylactic acid, 18 parts of super hydrophilic SiO2 nanoparticles, and 7 parts of additives.
[0156] Among them, the additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, consisting of 5 parts of epoxidized soybean oil, 0.5 parts of UV-531, 0.5 parts of antioxidant, 1680.5 parts of stearic acid, and 0.5 parts of iron oxide pigment.
[0157] The preparation method comprises the following steps:
[0158] S1. Add 100g of kaolinite to ether solution to prepare a solution with a mass concentration of 1wt%, then add 0.5g of sodium hexadecylbenzenesulfonate and 5g of perfluorooctyltriethoxysilane, use a turbine sand mill with a working energy consumption of 5kWh / kg to grind at 25°C for 60min, and obtain hydrophobic kaolinite with a particle size of 80nm after centrifugal separation.
[0159] S2. 100g of hydrophilic SiO2 nanoparticles were added to anhydrous ethanol to prepare a solution with a mass concentration of 1wt%, and then 5g of 3-aminopropyltriethoxysilane and 1g of DTAB were added. Hydrophilic groups were introduced on the surface of the hydrophilic nanoparticles with the assistance of microwaves. The output power of the microwave reactor was 800W, the reaction temperature was 180°C, and the reaction time was 20min to prepare super-hydrophilic SiO2 nanoparticles.
[0160] S3. Add 75 parts of polylactic acid, 18 parts of hydrophobic kaolinite and 7 parts of additives into a high-speed mixer and mix them at 165°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0161] 75 parts of polylactic acid, 18 parts of bamboo fiber and 7 parts of additives were added into a high-speed mixer for hot mixing at 165°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixtures reached 1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0162] 75 parts of polylactic acid, 18 parts of super-hydrophilic SiO2 nanoparticles and 7 parts of additives were added into a high-speed mixer for hot mixing at 165°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixture reached 1 kWh / kg, a hydrophilic layer masterbatch was obtained.
[0163] S4. Weigh 25% of the hydrophobic layer masterbatch, 50% of the mechanical support layer masterbatch, and 25% of the hydrophilic layer masterbatch as the masterbatch according to the mass percentage, and melt-blend the weighed hydrophobic layer masterbatch and PBAT at a mass ratio of 1:1 at 180°C to obtain a first masterbatch.
[0164] The mechanical support layer masterbatch and PBAT were melt blended at 180° C. in a mass ratio of 1:1 to obtain a second masterbatch.
[0165] The hydrophilic layer masterbatch and PBAT were melt blended at 180° C. in a mass ratio of 1:1 to obtain a third masterbatch.
[0166] The first masterbatch, the second masterbatch and the third masterbatch are added from different feed ports and co-extruded by biaxial stretching, and the extrusion die temperature is 170°C.
[0167] The longitudinal preheating temperature is 60°C, the longitudinal cooling temperature is 20°C, the longitudinal stretching temperature is 90°C, the longitudinal drawing setting temperature is 80°C, and the longitudinal stretching ratio is 2 times.
[0168] The transverse preheating temperature is 70°C, the transverse stretching temperature is 120°C, the transverse heat setting temperature is 100°C, the transverse cooling temperature is 20°C, and the transverse stretching ratio is 4 times. A composite membrane is prepared. The composite membrane is divided into three layers from the inside to the outside, namely, an inner hydrophilic layer, a middle mechanical support layer and an outer hydrophobic layer.
[0169] Subsequently, the surface of the inner hydrophilic layer was treated with oxygen plasma at 500 W for 20 min to prepare a self-watering, highly moisturizing biodegradable agricultural film with a thickness of 30 μm.
[0170] Example 3
[0171] A highly water-retaining biodegradable agricultural film with a self-absorbent structure, comprising the following raw materials in parts by weight:
[0172] Hydrophobic layer masterbatch: 75 parts of polylactic acid, 18 parts of hydrophobic montmorillonite nanosheets, and 7 parts of additives.
[0173] Mechanical support layer masterbatch: 75 parts of polylactic acid, 18 parts of lignin, and 7 parts of additives.
[0174] Hydrophilic layer masterbatch: 75 parts of polylactic acid, 18 parts of super hydrophilic SiO2 nanoparticles, and 7 parts of additives.
[0175] Among them, the additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, consisting of 5 parts of epoxidized soybean oil, 0.5 parts of UV-531, 0.5 parts of antioxidant, 1680.5 parts of stearic acid, and 0.5 parts of carbon black.
[0176] The preparation method comprises the following steps:
[0177] S1. 100 g of montmorillonite was added to an ether solution to prepare a solution with a mass concentration of 0.1 wt%, and then 2 g of sodium dodecyl sulfate and 5 g of perfluorooctylethyltrisilane were added. The solution was ground at 25°C for 120 min using a turbine sand mill with a working energy consumption of 10 kWh / kg, and centrifuged to obtain hydrophobic montmorillonite nanosheets with a particle size of 30 nm.
[0178] S2. 100g of hydrophilic TiO2 nanoparticles were added to anhydrous ethanol to prepare a solution with a mass concentration of 0.1wt%, and then 5g of 3-glycidyloxypropyltrimethoxysilane and 3g of sodium dodecyl sulfate (SDS) were added to introduce hydrophilic groups on the surface of the hydrophilic nanoparticles with the assistance of microwaves. The output power of the microwave reactor was 800W, the reaction temperature was 200°C, and the reaction time was 60min to prepare super hydrophilic TiO2 nanoparticles.
[0179] S3. Add 75 parts of polylactic acid, 18 parts of hydrophobic montmorillonite nanosheets and 7 parts of additives into a high-speed mixer and mix them at 170°C for 60 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0180] 75 parts of polylactic acid, 18 parts of lignin and 7 parts of additives were added into a high-speed mixer for hot mixing at 170°C for 60 minutes. When the ratio of mixing output energy to the mass of all the mixtures reached 1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0181] 75 parts of polylactic acid, 18 parts of super-hydrophilic SiO2 nanoparticles and 7 parts of additives were added into a high-speed mixer for hot mixing at 170°C for 60 minutes. When the ratio of mixing output energy to the mass of all the mixtures reached 1 kWh / kg, a hydrophilic layer masterbatch was obtained.
[0182] S4. Weigh 30% of the hydrophobic layer masterbatch, 50% of the mechanical support layer masterbatch, and 20% of the hydrophilic layer masterbatch as the masterbatch according to the mass percentage, and melt-blend the weighed hydrophobic layer masterbatch and PBAT at a mass ratio of 7:3 at 170°C to obtain a first masterbatch.
[0183] The mechanical support layer masterbatch and PBAT were melt blended at 170° C. in a mass ratio of 7:3 to obtain a second masterbatch.
[0184] The hydrophilic layer masterbatch and PBAT were melt-blended at 170° C. in a mass ratio of 7:3 to obtain a third masterbatch.
[0185] The first masterbatch, the second masterbatch and the third masterbatch are added from different feed ports and co-extruded in two directions with the extrusion die temperature being 190°C.
[0186] The longitudinal preheating temperature is 80°C, the longitudinal stretching temperature is 100°C, the longitudinal drawing setting temperature is 110°C, the longitudinal cooling temperature is 25°C, and the longitudinal stretching ratio is 1.5 times.
[0187] The transverse preheating temperature is 90°C, the transverse stretching temperature is 110°C, the transverse heat setting temperature is 120°C, the transverse cooling temperature is 25°C, and the transverse stretching ratio is 1.5 times to prepare a composite membrane. The composite membrane is divided into three layers from the inside to the outside, namely, an inner hydrophilic layer, a middle mechanical support layer and an outer hydrophobic layer.
[0188] Subsequently, the surface of the inner hydrophilic layer was treated with oxygen plasma at 700 W for 10 min to prepare a self-watering, highly moisturizing biodegradable agricultural film with a thickness of 40 μm.
[0189] Example 4
[0190] A highly water-retaining biodegradable agricultural film with a self-absorbent structure, comprising the following raw materials in parts by weight:
[0191] Hydrophobic layer masterbatch: 78 parts of polylactic acid, 16 parts of hydrophobic vermiculite nanosheets, and 7.2 parts of additives.
[0192] Mechanical support layer masterbatch: 78 parts of polylactic acid, 16 parts of chitosan, and 7.2 parts of additives.
[0193] Hydrophilic layer masterbatch: 78 parts of polylactic acid, 16 parts of super hydrophilic SiO2 nanoparticles, and 7.2 parts of additives.
[0194] Among them, the additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, consisting of 4.5 parts of epoxidized soybean oil, 0.8 parts of antioxidant 3000, 1 part of UV-327, 1 part of zinc stearic acid, and 0.9 part of phthalocyanine blue.
[0195] The preparation method comprises the following steps:
[0196] S1. Add 100g of vermiculite into anhydrous ethanol solution to prepare a solution with a mass concentration of 0.1wt%, then add 0.1g of sodium hexadecylbenzenesulfonate and 0.1g of perfluorooctyl propylene, use a turbine sand mill with a working energy consumption of 1kWh / kg to grind at 80°C for 20min, and centrifuge to obtain hydrophobic vermiculite nanosheets with a particle size of 100nm.
[0197] S2. 70g of hydrophilic SiO2 nanoparticles were added to anhydrous ethanol to prepare a solution with a mass concentration of 0.1wt%, and then 30g of 3-aminopropyltriethoxysilane and 7g of dodecyl betaine were added and dispersed in anhydrous ethanol. Hydrophilic groups were introduced on the surface of the hydrophilic nanoparticles with the assistance of microwaves. The output power of the microwave reactor was 1000W, the reaction temperature was 80°C, and the reaction time was 120min to prepare super hydrophilic SiO2 nanoparticles.
[0198] S3. Add 78 parts of polylactic acid, 16 parts of hydrophobic vermiculite nanosheets, and 7.2 parts of additives into a high-speed mixer and mix them at 120°C for 120 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 0.1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0199] 78 parts of polylactic acid, 16 parts of chitosan and 7.2 parts of additives were added into a high-speed mixer for hot mixing at 120°C for 120 minutes. When the ratio of mixing output energy to the mass of all the mixtures reached 0.1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0200] 78 parts of polylactic acid, 16 parts of superhydrophilic SiO2 nanoparticles and 7.2 parts of additives were added into a high-speed mixer for hot mixing at 120°C for 120 minutes. When the ratio of mixing output energy to the mass of all the mixture reached 0.1 kWh / kg, a hydrophilic layer masterbatch was obtained.
[0201] S4. Weigh 30% of the hydrophobic layer masterbatch, 35% of the mechanical support layer masterbatch, and 35% of the hydrophilic layer masterbatch according to mass percentage, and melt-blend the weighed hydrophobic layer masterbatch and polyhydroxyalkanoate at a mass ratio of 6:4 at 180° C. to obtain a first masterbatch.
[0202] The mechanical support layer masterbatch and polyhydroxyalkanoate were melt-blended at 180° C. in a mass ratio of 6:4 to obtain a second masterbatch.
[0203] The hydrophilic layer masterbatch and the polyhydroxyalkanoate were melt-blended at 180° C. in a mass ratio of 6:4 to obtain a third masterbatch.
[0204] The first masterbatch, the second masterbatch and the third masterbatch are added from different feed ports and co-extruded by biaxial stretching, and the extrusion die temperature is 160°C.
[0205] The longitudinal preheating temperature is 80°C, the longitudinal cooling temperature is 30°C, the longitudinal stretching temperature is 130°C, the longitudinal drawing setting temperature is 100°C, and the longitudinal stretching ratio is 2.5 times.
[0206] The transverse preheating temperature is 100°C, the transverse stretching temperature is 110°C, the transverse heat setting temperature is 100°C, the transverse cooling temperature is 30°C, and the transverse stretching ratio is 3 times to prepare a composite membrane. The composite membrane is divided into three layers from the inside to the outside, namely, an inner hydrophilic layer, a middle mechanical support layer and an outer hydrophobic layer.
[0207] Subsequently, the surface of the inner hydrophilic layer was treated with oxygen plasma at 500 W for 20 min to prepare a self-watering and highly moisturizing biodegradable agricultural film.
[0208] Example 5
[0209] A highly water-retaining biodegradable agricultural film with a self-absorbent structure, comprising the following raw materials in parts by weight:
[0210] Hydrophobic layer masterbatch: 80 parts of polylactic acid, 12.5 parts of hydrophobic illite nanosheets, and 7.5 parts of additives.
[0211] Mechanical support layer masterbatch: 80 parts of polylactic acid, 12.5 parts of lignin, and 7.5 parts of additives.
[0212] Hydrophilic layer masterbatch: 80 parts of polylactic acid, 12.5 parts of super hydrophilic SiO2 nanoparticles, and 7.5 parts of additives.
[0213] Among them, the additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, consisting of 4 parts of epoxidized soybean oil, 1680.7 parts of antioxidant, 0.7 parts of UV-531, 0.7 parts of zinc stearic acid, and 0.5 parts of titanium dioxide.
[0214] The preparation method comprises the following steps:
[0215] S1. Add 100g of illite to a methanol solution to prepare a solution with a mass concentration of 0.1wt%, then add 5g of sodium dodecyl polyoxyethylene ether sulfate and 10g of perfluorooctane sulfonyl fluoride, use a turbine sand mill with a working energy consumption of 1kWh / kg to grind at 60°C for 30min, and centrifuge to obtain hydrophobic illite nanosheets with a particle size of 100nm.
[0216] S2. 90g of hydrophilic SiO2 nanoparticles were added to anhydrous ethanol to prepare a solution with a mass concentration of 0.1wt%, and then 10g of 3-aminopropyltriethoxysilane and 7.2g of CTAB were added and dispersed in anhydrous ethanol. Hydrophilic groups were introduced on the surface of the hydrophilic nanoparticles with the assistance of microwaves. The output power of the microwave reactor was 500W, the reaction temperature was 100°C, and the reaction time was 100min to prepare super hydrophilic SiO2 nanoparticles.
[0217] S3. Add 80 parts of polylactic acid, 12.5 parts of hydrophobic illite nanosheets, and 7 parts of additives into a high-speed mixer for hot mixing at a temperature of 300°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 0.1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0218] 80 parts of polylactic acid, 12.5 parts of lignin and 7 parts of additives were added into a high-speed mixer for hot mixing at 300°C for 10 minutes. When the ratio of mixing output energy to the mass of all mixtures reached 0.1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0219] 80 parts of polylactic acid, 12.5 parts of super-hydrophilic SiO2 nanoparticles and 7 parts of additives were added into a high-speed mixer for hot mixing at 300°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixtures reached 0.1 kWh / kg, a hydrophilic layer masterbatch was obtained.
[0220] S4. Weigh 30% of the hydrophobic layer masterbatch, 40% of the mechanical support layer masterbatch, and 30% of the hydrophilic layer masterbatch according to mass percentage, and melt-blend the weighed hydrophobic layer masterbatch and polycaprolactone at a mass ratio of 9:1 at 180°C to obtain a first masterbatch.
[0221] The mechanical support layer masterbatch and polycaprolactone were melt-blended at 180° C. in a mass ratio of 9:1 to obtain a second masterbatch.
[0222] The hydrophilic layer masterbatch and polycaprolactone were melt-blended at 180° C. in a mass ratio of 9:1 to obtain a third masterbatch.
[0223] The first masterbatch, the second masterbatch and the third masterbatch are added from different feed ports and co-extruded by biaxial stretching, and the extrusion die temperature is 160°C.
[0224] The longitudinal preheating temperature is 90°C, the longitudinal cooling temperature is 20°C, the longitudinal stretching temperature is 100°C, the longitudinal drawing setting temperature is 110°C, and the longitudinal stretching ratio is 2.5 times.
[0225] The transverse preheating temperature is 90°C, the transverse stretching temperature is 110°C, the transverse heat setting temperature is 120°C, the transverse cooling temperature is 30°C, and the transverse stretching ratio is 3 times to prepare a composite membrane. The composite membrane is divided into three layers from the inside to the outside, namely, an inner hydrophilic layer, a middle mechanical support layer and an outer hydrophobic layer.
[0226] Subsequently, the surface of the inner hydrophilic layer film was treated with oxygen plasma at 700W for 10 minutes to prepare a self-watering and highly moisturizing biodegradable agricultural film.
[0227] Comparative Example 1
[0228] This comparative example prepares a single-layer agricultural film, which is composed of the following raw materials in parts by weight:
[0229] Mechanical support layer masterbatch: 80 parts of polylactic acid, 12.5 parts of wood fiber, and 7.5 parts of additives.
[0230] The auxiliary agent is composed of 5 parts of epoxidized soybean oil, 0.5 parts of antioxidant BHT, 0.5 parts of UV-327, 0.5 parts of zinc stearic acid, and 1 part of carbon black.
[0231] The preparation method comprises the following steps:
[0232] S1. Add 80 parts of polylactic acid, 12.5 parts of wood fiber, and 7.5 parts of additives into a high-speed mixer for hot mixing, and mix at a temperature of 150°C for 60 minutes. The masterbatch is obtained when the ratio of the mixing output energy to the mass of all the mixture reaches 0.1 kWh / kg.
[0233] S2. Weigh the masterbatch and PBS in a mass ratio of 7:3, and then co-extrude the masterbatch and PBS by biaxial stretching at an extrusion die temperature of 200°C.
[0234] The longitudinal preheating temperature is 90°C, the longitudinal stretching temperature is 100°C, the longitudinal drawing setting temperature is 120°C, the longitudinal cooling temperature is 40°C, and the longitudinal stretching ratio is 3 times.
[0235] The transverse preheating temperature is 110°C, the transverse stretching temperature is 130°C, the transverse heat setting temperature is 140°C, the transverse cooling temperature is 50°C, and the transverse stretching ratio is 1.5 times to prepare the biodegradable agricultural film.
[0236] Comparative Example 2
[0237] A biodegradable agricultural film is composed of the following raw materials in parts by weight:
[0238] Hydrophobic layer masterbatch: 80 parts of polylactic acid, 12.5 parts of hydrophobic montmorillonite nanosheets, and 7.5 parts of additives.
[0239] Mechanical support layer masterbatch: 80 parts of polylactic acid, 12.5 parts of wood fiber, and 7.5 parts of additives.
[0240] Among them, the additives in the hydrophobic layer masterbatch and the mechanical support layer masterbatch are the same, consisting of 5 parts of epoxidized soybean oil, 0.5 parts of antioxidant BHT, 0.5 parts of UV-327, 0.5 parts of zinc stearic acid, and 1 part of carbon black.
[0241] The preparation method comprises the following steps:
[0242] S1. 100 g of montmorillonite was added to an ether solution to prepare a solution with a mass concentration of 0.1 wt%, and then 1 g of sodium dodecylbenzene sulfonate and 0.2 g of perfluorooctanethiol were added. The solution was ground at 25 ° C for 30 min using a turbine sand mill with a working energy consumption of 1 kWh / kg, and hydrophobic montmorillonite nanosheets with a particle size of 100 nm were obtained by centrifugal separation.
[0243] S2. Add 80 parts of polylactic acid, 12.5 parts of hydrophobic montmorillonite nanosheets and 7.5 parts of additives into a high-speed mixer and mix them at 150°C for 60 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 0.1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0244] 80 parts of polylactic acid, 12.5 parts of wood fiber and 7.5 parts of additives were added into a high-speed mixer for hot mixing at 150°C for 60 minutes. When the ratio of mixing output energy to the mass of all mixtures reached 0.1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0245] S4. Weigh 40% of the hydrophobic layer masterbatch and 60% of the mechanical support layer masterbatch according to mass percentage, melt-blend the weighed hydrophobic layer masterbatch and PBS at a mass ratio of 7:3 at 180° C. to obtain a first masterbatch.
[0246] The mechanical support layer masterbatch and PBS were melt-blended at 180° C. in a mass ratio of 7:3 to obtain a second masterbatch.
[0247] The first masterbatch and the second masterbatch are added from different feed ports and co-extruded by biaxial stretching. The extrusion die temperature is 200°C.
[0248] The longitudinal preheating temperature is 90°C, the longitudinal stretching temperature is 100°C, the longitudinal drawing setting temperature is 120°C, the longitudinal cooling temperature is 40°C, and the longitudinal stretching ratio is 3 times.
[0249] The transverse preheating temperature is 110°C, the transverse stretching temperature is 130°C, the transverse heat setting temperature is 140°C, the transverse cooling temperature is 50°C, and the transverse stretching ratio is 1.5 times to prepare a composite film. The composite film consists of a mechanical support layer and an outer hydrophobic layer from the inside to the outside to prepare a biodegradable agricultural film with a thickness of 50 μm.
[0250] Comparative Example 3
[0251] This comparative example is composed of the following raw materials in parts by weight:
[0252] Hydrophobic layer masterbatch: 75 parts of polylactic acid, 18 parts of hydrophobic kaolinite, and 7 parts of additives.
[0253] Mechanical support layer masterbatch: 75 parts of polylactic acid, 18 parts of bamboo fiber, and 7 parts of additives.
[0254] Hydrophilic layer masterbatch: 75 parts of polylactic acid, 18 parts of super hydrophilic SiO2 nanoparticles, and 7 parts of additives.
[0255] The additives are 5 parts of epoxidized soybean oil, 0.5 parts of UV-531, 0.5 parts of antioxidant, 1680.5 parts of stearic acid, and 0.5 parts of iron oxide pigment.
[0256] The preparation method comprises the following steps:
[0257] S1. Add 100g of kaolinite to an ether solution to prepare a solution with a mass concentration of 1wt%, then add 0.5g of sodium hexadecylbenzenesulfonate and 5g of perfluorooctyltriethoxysilane, and grind at 25°C for 60min using a turbine sand mill with a working energy consumption of 5kWh / kg. After centrifugal separation, hydrophobic kaolinite with a particle size of 80nm is obtained.
[0258] S2. 100g of hydrophilic SiO2 nanoparticles were added to anhydrous ethanol to prepare a solution with a mass concentration of 1wt%, and then 5g of 3-aminopropyltriethoxysilane and 1g of DTAB were added. Hydrophilic groups were introduced on the surface of the hydrophilic nanoparticles with the assistance of microwaves. The output power of the microwave reactor was 800W, the reaction temperature was 180°C, and the reaction time was 20min to prepare super-hydrophilic SiO2 nanoparticles.
[0259] S3. Add 75 parts of polylactic acid, 18 parts of hydrophobic kaolinite and 7 parts of additives into a high-speed mixer and mix them at 165°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixture reaches 1 kWh / kg, a hydrophobic layer masterbatch is obtained.
[0260] 75 parts of polylactic acid, 18 parts of bamboo fiber and 7 parts of additives were added into a high-speed mixer for hot mixing at 165°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixtures reached 1 kWh / kg, a mechanical support layer masterbatch was obtained.
[0261] 75 parts of polylactic acid, 18 parts of super-hydrophilic SiO2 nanoparticles and 7 parts of additives were added into a high-speed mixer for hot mixing at 165°C for 10 minutes. When the ratio of mixing output energy to the mass of all the mixture reached 1 kWh / kg, a hydrophilic layer masterbatch was obtained.
[0262] S4. Weigh 25% of the hydrophobic layer masterbatch, 50% of the mechanical support layer masterbatch, and 25% of the hydrophilic layer masterbatch according to the mass percentage, and melt-blend the weighed hydrophobic layer masterbatch and PBAT at a mass ratio of 1:1 at 150°C to obtain a first masterbatch.
[0263] The mechanical support layer masterbatch and PBAT were melt blended at 150° C. in a mass ratio of 1:1 to obtain a second masterbatch.
[0264] The hydrophilic layer masterbatch and PBAT were melt blended at 150° C. in a mass ratio of 1:1 to obtain a third masterbatch.
[0265] The first masterbatch, the second masterbatch and the third masterbatch are added from different feeding ports and co-extruded at 100°C to obtain a functional biodegradable agricultural film. Subsequently, the surface of the film after the hydrophilic layer is stretched is treated with oxygen plasma at 500W for 20 minutes to prepare the biodegradable agricultural film.
[0266] The following is a structural characterization and performance test of the degradable agricultural films prepared in the examples and comparative examples.
[0267] Mechanical properties test: The obtained film was cut to obtain tensile specimens, and the tensile properties were tested using a universal tensile machine (model 4403, sensor 100N) from Instron, USA, according to the ASTM D638-2003 plastic tensile properties test standard of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.
[0268] Moisture barrier performance of ground film: According to GB / T 1037 Test method for water vapor permeability of plastic film and sheet, use humidity control instrument and humidity sensor to place the sample in high humidity and low humidity environment respectively, measure the humidity difference on both sides, and calculate the transmittance.
[0269] Water absorption test: Prepare a certain number of material samples and ensure that the sample sizes are consistent. Dry the samples at 60°C to constant weight and record the initial weight (W0). Place the samples under different humidity conditions (in an environmental chamber with 90% relative humidity) and ensure that the number of samples under each humidity condition is consistent. Keep for 24 hours to ensure that the sample fully absorbs water. Take out the sample, quickly absorb excess water on the surface with filter paper, and weigh the sample (W1). Water absorption calculation: η = (1-W0 / W1) × 100%
[0270] Water retention test: Place the sample (W1) after water absorption in a constant temperature and humidity chamber for a certain period of time to conduct a water retention test. Experimental steps: Maintain humidity: Place the sample after water absorption under different environmental humidity conditions (in an environmental chamber with 90% relative humidity) to simulate the water retention performance under different environmental conditions. Take out the sample every 2 hours and weigh the sample (W2). Water retention calculation: η = (W2-W0) / (W1-W0)×100%.
[0271] Water contact angle test: By dropping a drop of water on the surface of the material and then using an optical contact angle instrument to measure the contact angle formed by the water drop on the surface of the material, the surface hydrophilicity or hydrophobicity of the material is evaluated.
[0272] Table 1 Test results of mechanical properties, water vapor permeability, water absorption and water retention of biodegradable agricultural films
[0273]
[0274]
[0275] Compared with Example 1 and Comparative Example 1, the degradable agricultural film prepared in Comparative Example 1 lacks an inner hydrophilic layer and an outer hydrophobic layer, and the degradable agricultural film prepared in Comparative Example 2 lacks an inner hydrophilic layer. As can be seen from Table 1, the introduction of layered silicates and super-hydrophilic nanoparticles improves the strength and toughness of the material. The tensile strength and elongation at break of Example 1 are significantly higher than those of Comparative Example 1, mainly because the high aspect ratio of layered silicates enables them to form a reinforced network similar to a "nano wall structure" in the polymer matrix. This structure enables the material to better disperse stress when subjected to force, thereby improving strength. The interfacial interaction between the super-hydrophilic nanoparticles and the matrix polymer is significantly enhanced, so that the stress is more evenly distributed in the material, reducing local stress concentration, thereby improving the overall mechanical strength, and making the material more suitable for practical applications.
[0276] Comparing the water absorption and water retention of Example 1 and Comparative Example 1, Example 1 shows a higher water absorption and better water retention performance. The presence of the hydrophilic layer enables the agricultural film to effectively absorb moisture in the environment and evenly distribute it to the soil, ensuring that the roots of the crops are continuously supplied with water. As a result, the agricultural film in Example 1 exhibits a stronger water retention capacity and a longer moisture retention effect. The agricultural film in Comparative Example 2 lacks a hydrophilic layer, which causes it to be unable to effectively absorb and retain moisture, affecting the performance of the agricultural film under drought conditions. This shows that the hydrophilic layer is crucial to improving the water retention performance of the agricultural film. The outer hydrophobic layer effectively prevents excessive evaporation of external moisture and protects the moisture in the soil. The hydrophobic layer can also reduce water loss caused by changes in the external environment (such as high temperature), thereby extending the service life and validity period of the agricultural film. The agricultural film in Comparative Example 1 lacks an outer hydrophobic layer, which accelerates the evaporation rate of water in a high temperature or dry environment, affecting the normal growth of crops. This is because the self-absorbent water-retaining biodegradable agricultural film prepared by the present invention has a Janus structure. This structure has the characteristics of hydrophilicity and hydrophobicity gradient distribution, so that the agricultural film can better utilize and regulate the absorption, retention and evaporation of water, which has practical application value in water resource management. The barrier performance test results can show the applicability of the material in agricultural film applications. The Janus structure and self-absorbent function significantly improve the water retention and barrier properties of the material, making it have broad application prospects in agriculture and packaging and other fields.
[0277] Compared with Example 3, Example 2 is prepared by biaxial stretching. Compared with the conventional casting co-extrusion preparation method, the biaxial stretching method promotes the nanosheets to be arranged in parallel along the stretching direction in the polymer matrix during the preparation process, and at the same time makes the nanosheets more evenly distributed in the polymer matrix, and the interfacial bonding force is enhanced, thereby effectively transmitting stress and reducing microcracks or stress concentration in the matrix. The introduction of nanosheets combined with biaxial stretching helps to improve the elongation at break of the material, so that the material can better absorb energy and is not prone to breakage when stretched, thereby improving the mechanical strength and toughness of the agricultural film.
[0278] Table 2 Test results of water contact angle of biodegradable agricultural film
[0279]
[0280] It should be noted that in Table 2, * indicates that there is no such data.
[0281] As can be seen from Table 2, in Examples 1-5, the surface energy of the material is improved by adding hydrophilic nanofillers, making it easier for water droplets to spread on the surface, thereby reducing the contact angle. In Examples 1-5, the contact angle of the outer hydrophobic layer is higher, indicating better hydrophobic performance. The hydrophobic nanofiller increases the roughness of the substrate surface, thereby improving the hydrophobicity. The hydrophobicity of Comparative Examples 1-3 is slightly lower than that of the embodiment, which may be due to uneven distribution of the filler or weak binding force with the substrate material, resulting in a slight decrease in hydrophobicity.
[0282] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0283] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film, characterized in that: The self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film is composed of an outer hydrophobic layer, an intermediate mechanical support layer and an inner hydrophilic layer co-extruded; The outer hydrophobic layer is composed of a hydrophobic layer masterbatch and polyester in a mass ratio of 5 to 9:1 to 5, and the hydrophobic layer masterbatch is prepared by blending and granulating the following components in mass parts: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of hydrophobic layered nanosheets and 7 to 7.5 parts of an auxiliary agent; The intermediate mechanical support layer is composed of a mechanical support layer masterbatch and polyester in a mass ratio of 5 to 9:1 to 5, and the mechanical support layer masterbatch is prepared by blending and granulating the following components in mass parts: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of bio-based filler and 7 to 7.5 parts of additives; The inner hydrophilic layer is composed of a hydrophilic layer masterbatch and polyester in a mass ratio of 5-9:1-5. The hydrophilic layer masterbatch is made by blending and granulating the following components in mass parts: 75-80 parts of polylactic acid, 12.5-18 parts of superhydrophilic nanoparticles and 7-7.5 parts of additives.
2. The self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 1, characterized in that: The hydrophobic layered nanosheets are prepared according to the following steps: The layered silicate mineral, the hydrophobic surfactant and the fluorinating agent are subjected to shear exfoliation to cause a fluorination reaction, and fluorine groups are introduced into the layered silicate mineral to obtain a hydrophobic layered nanosheet; The mass ratio of the layered silicate mineral to the fluoriding agent is 100:0.1-10; the mass ratio of the layered silicate mineral to the hydrophobic surfactant is 100:0.1-5, and the shear exfoliation is performed by grinding at 20°C-80°C for 20min-120min.
3. The self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 1, characterized in that: Superhydrophilic nanoparticles are prepared according to the following steps: In a solvent system, hydrophilic nanoparticles, a hydrophilic bridging agent and a hydrophilic surfactant are mixed, and under the assistance of microwaves, condensation and covalent bonding reactions occur to introduce the hydrophilic groups of the hydrophilic surfactant into the surface of the hydrophilic nanoparticles to prepare super-hydrophilic nanoparticles.
4. The self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 3, characterized in that: The mass ratio of the hydrophilic nanoparticles to the hydrophilic bridging agent is 70-100:5-30; the mass ratio of the hydrophilic nanoparticles to the hydrophilic surfactant is 1:0.01-0.1; In the condensation and covalent bonding reactions, the microwave output power is 100W to 1500W, the reaction temperature is 80°C to 200°C, and the reaction time is 20min to 120min.
5. The self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 1, characterized in that: The hydrophobic layer masterbatch accounts for 15% to 30% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; The mechanical support layer masterbatch accounts for 35% to 60% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; The hydrophilic layer masterbatch accounts for 20% to 35% of the total mass of the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch; the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch total 100%.
6. The self-absorbent structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 1, characterized in that: The bio-based filler is one or more of wood fiber, bamboo fiber and corn straw; The additives in the hydrophobic layer masterbatch, the mechanical support layer masterbatch and the hydrophilic layer masterbatch are the same, and the additives are composed of the following components by mass: 4 to 5 parts of plasticizer, 0.5 to 1 part of antioxidant, 0.5 to 1 part of ultraviolet absorber, 0.5 to 1 part of heat stabilizer and 0.5 to 1 part of dye; The polyester is one or more of polybutylene succinate, polyhydroxyalkanoate, polyethylene terephthalate / polycaprolactone blend and polycaprolactone.
7. A method for preparing the self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film according to any one of claims 1 to 6, characterized in that: The following steps are involved: Weigh the following components of the hydrophobic layer masterbatch according to the following weight parts: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of hydrophobic layered nanosheets, and 7 to 7.5 parts of an auxiliary agent; blend and granulate the polylactic acid, the hydrophobic layered nanosheets, and the auxiliary agent to obtain a hydrophobic layer masterbatch; Weigh the following components of the mechanical support layer masterbatch according to the following weight parts: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of bio-based fillers, and 7 to 7.5 parts of additives; blend and granulate the polylactic acid, bio-based fillers, and additives to obtain a mechanical support layer masterbatch; Weigh the following components of the hydrophilic layer masterbatch according to the following weight parts: 75 to 80 parts of polylactic acid, 12.5 to 18 parts of super-hydrophilic nanoparticles, and 7 to 7.5 parts of an auxiliary agent; blend and granulate the polylactic acid, super-hydrophilic nanoparticles, and the auxiliary agent to obtain a hydrophilic layer masterbatch; The hydrophobic layer masterbatch and polyester are melt-blended to obtain a first masterbatch, the mechanical support layer masterbatch and polyester are melt-blended to obtain a second masterbatch, and the hydrophilic layer masterbatch and polyester are melt-blended to obtain a third masterbatch. The first masterbatch, the second masterbatch and the third masterbatch are co-extruded by biaxial stretching to obtain a water-retaining biodegradable agricultural film with a self-absorbent structure.
8. The method for preparing the self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 7, characterized in that: When preparing the first masterbatch, the second masterbatch and the third masterbatch, the melt blending temperature and time are the same, the melt blending temperature is 120° C. to 300° C., and the melt blending time is 10 min to 120 min.
9. The method for preparing the self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 7, characterized in that: In the biaxial stretching co-extrusion step, the extrusion die temperature is 170° C. to 200° C.; Longitudinal preheating temperature is 60℃~90℃, longitudinal cooling temperature is 20℃~40℃, longitudinal stretching temperature is 90℃~130℃, and longitudinal drawing setting temperature is 80℃~120℃; Transverse preheating temperature 70℃~110℃, transverse stretching temperature 100℃~140℃, transverse heat setting temperature 100℃~140℃, transverse cooling temperature 20℃~50℃; The transverse stretching ratio is 1.5 to 4 times, and the longitudinal stretching ratio is 1.5 to 3 times.
10. The method for preparing the self-water-absorbing structure water-retaining and moisture-retaining biodegradable agricultural film according to claim 7, characterized in that: The invention also includes subjecting the surface of the hydrophilic layer of the composite film obtained by biaxial stretching co-extrusion to oxygen plasma treatment; The oxygen plasma treatment is carried out at 500W to 1500W for 0.5min to 20min.
Citation Information
Patent Citations
Multi-layer co-extrusion based biodegradable mulch film and preparation method thereof
CN106519602A
Wetting-resistant and oil-stain-resistant Janus type distillation membrane as well as preparation method and application thereof
CN111744369A
Transparent multilayer biodegradable polyester agricultural film as well as preparation method and application thereof
CN112602515A
Degradable mulching film capable of improving water resistance, heat preservation, soil moisture conservation and mechanical properties through lamination compounding and preparation method of degradable mulching film
CN115302741A
High-barrier biodegradable composite film and preparation process thereof
CN115593061A
Cited By
Multifunctional full-degradable mulching film with water taking, slow release and soil improvement functions and preparation method of multifunctional full-degradable mulching film
CN120419429A
Micro-nano laminated composite structure biodegradable mulching film and preparation method thereof
CN121821918A